Salutogenic interventions and health effects: a scoping review of the literature - Óscar Suárez Álvarez; María Teresa Ruiz-Cantero; Viola Cassetti; Rafael Cofiño; Carlos Álvarez-Dardet (Elsevier, 2021)
Objective: To explore the typology of implemented salutogenic interventions and the health effects described by the authors. Method: A scoping review of the literature published (PubMed, Embase, Web of Science and Scopus) over the last ten years (2007-2016) was conducted. Articles that included interventions with assessments of health outcomes were selected for this review. The kappa index (86.4%) was calculated for the classification and extraction of information. Results: 61 papers were selected out of the 676 works identified. These were categorized into individual, grouped, mixed and intersectoral interventions. A total of 85% of the interventions described positive effects. Adverse effects were not reported. Methodological limitations were identified in 75% of the papers. The interventions addressed a large variety of topics, especially in the field of mental health and chronic diseases. Collective actions described more positive effects. Intersectoral actions were the only type of interventions to have approached the impact of mortality reduction. Conclusions: Findings support the existence of positive health effects of salutogenic approaches. Important methodological limitations were identified, such as biases in the selection of participants and sample sizes. Studies need to be conducted with improved monitoring and evaluation designs. A more robust theoretical framework and tools to evaluate the salutogenic contents are needed. Resumen: Objetivo: Conocer el tipo de las intervenciones salutogénicas identificadas en la literatura científica y los efectos descritos por los autores en la salud de la población. Método: Se realizó una scoping review de trabajos publicados entre los años 2007 y 2016 en español, inglés y francés en PubMed, Embase, Web of Science y Scopus. Se seleccionaron y clasificaron trabajos de investigación que contemplaran una intervención con evaluación de resultados en salud. Se calculó el índice kappa (86,4%) para la clasificación y la extracción de la información. Resultados: Se seleccionaron 61 trabajos de investigación entre 676 trabajos identificados. Se clasificaron en intervenciones individuales, grupales, mixtas e intersectoriales. El 85% de las intervenciones describieron efectos positivos. No se encontraron efectos adversos. Se observaron limitaciones metodológicas en el 75% de los trabajos. Las intervenciones abordaban gran variedad de temas, especialmente en el campo de la salud mental y las enfermedades crónicas. Las intervenciones colectivas describen más efectos positivos. Las actuaciones intersectoriales representan el único tipo de intervenciones que ha abordado el impacto en la reducción de la mortalidad. Conclusiones: Los hallazgos descritos sugieren la existencia de efectos positivos para la salud. Se identifican importantes limitaciones metodológicas. Es necesario desarrollar estudios en mejores condiciones de control, así como marcos teóricos más robustos y herramientas que permitan evaluar el contenido salutogénico de las intervenciones.